A Study of the Relationship of Job Satisfaction with Self Efficacy, Adaptation, and Occupational Stress Among the Teachers in the Changing Educational Policy in India (International Journal of Innovative Research in Engineering & Management, 2023)
Teachers always play important role in the  teaching learning process. Recent changes in India’s  educational policy have attracted several thinkers and  researchers to explore the teaching learning wellbeing of  Indian education system. School teachers are very  important part of this educational infrastructure. Present  research is dedicated to the primary schools’ teachers and  their job satisfaction. A school teacher has to face multiple  challenges related with students and management.  Researchers have used a questionnaire with 30 questions.  A survey has been conducted among 500 primary school  teachers in Patna district, Bihar. The present study shows  that their self-efficacy, adaption and management of  occupational stress plays great role in their job satisfaction.
Keywords: Job Satisfaction with Self-Efficacy; Adaptation; Occupational Stress